A review of teenage pregnancy research in Malaysia - Mohd Suan, Mohd Azri; Ismail, Adibah Hanim; Ghazali, Haliza (Malaysian Medical Association, 2015)
Objective: To summarise the published research on teenage pregnancy in Malaysia, discuss the impact of the findings on clinical practice, and identify gaps in teenage pregnancy research in Malaysia. Methods: There were 31 articles related to teen pregnancy found after searching a database dedicated to indexing all original clinical research data published in Malaysia from year 2000 to 2014. Twenty-seven articles (including reports from the National Obstetrics Registry) were selected and reviewed on the basis of clinical relevance and future research implications. This literature review has been divided into eight sections: epidemiology, age at first marriage, adolescent fertility rate, unmarried childbearing, risk factors, maternal risks and neonatal outcome, future plan after delivery, and contraceptive use. Results: More than 19,000 births to teenage mothers were recorded each year between 2009 and 2011. Adolescent fertility rates were recorded at 6 births per 1000 women ages 15-19 years in 2013. Many of these births were from unwed pregnancies, which accounted for 1.99% of total deliveries. A majority of young mothers were willing to take care of their baby, although some of them planned to put their baby up for adoption. Risk factors for teenage pregnancy were found to be similar to those published in studies worldwide. Conclusion: More research is needed to better understand the issue of teen pregnancy. For the best results, collaborative studies among nationwide hospitals and institutions should be the way forward.